The effect of theraband rotator cuff strengthening for archery athletes accuracy - Riko Adi Baskoro; Mugiyo Hartono; Sri Sumartiningsih; Dewangga Yudhistira (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
AbstractArchery is an accuracy sport that requires muscle strength to get good accuracy. This study aimed to analyze the effect of theraband rotator cuff strengthening exercise method and the core stability exercise method on the results of archery accuracy for archery athletes in Klaten district. This study used a quasi-experimental method with a two-factorial design. The population of this study were 80 archery athletes in Klaten district who were sampled from the SMART club, the SETRO ARCHERY club, and the SAROTAMA club. The sampling technique used purposive sampling and a total samples were 40 athletes. Data analysis used Analysis of Variance (Anava) at a significance level of α = 0.05. The results are 1) slow and fast theraband rotator cuff strengthening exercise methods were obtained (p=0.843 0.05), static and dynamic Core Stability Exercise exercises were obtained (p=0.921 0.05), interactions of theraband rotator cuff strengthening exercise methods slow and static core stability exercise obtained value (p=0.978 0.05), interaction of slow theraband rotator cuff strengthening exercise method and dynamic core stability exercise obtained value (p=0.986 0.05), interaction of fast theraband rotator cuff strengthening exercise method and static core stability exercise value obtained (p=0.978 0.05), interaction of fast rotator cuff strengthening theraband exercise method and dynamic core stability exercise obtained value (p=0.978 0.05). The conclusions are 1). There is the effect of the rotator cuff strengthening theraband exercise method, slow and fast pulling. 2). There is an influence of static and dynamic core stability exercise methods. 3). Theraband and core stability exercise methods affects the athletes’ accuracy, but there is no significant difference in exercise effect between groups.